EFFECTIVENESS OF ORAL COLLAGEN SUPPLEMENTATION IN IMPROVING SKIN ELASTICITY AND HYDRATION: A LITERATURE REVIEW - Patrycja Markowicz; Anna Skrzypek; Maciej Hutkowski; Mikołaj Zbrożek; Zuzanna Chwostek; Bartłomiej Kosiarski; Paulina Biedroń; Hanna Maruchniak; Wiktoria Marzec; Krzysztof Biłyk (International Journal of Innovative Technologies in Social Science, 2026)
Background: Oral collagen supplementation has gained popularity as a strategy for supporting skin health, particularly in the context of aging and disturbances of the extracellular matrix. Evidence suggests that hydrolyzed collagen peptides may affect skin hydration and elasticity by stimulating fibroblast activity and collagen synthesis. Aim: The aim of this review was to assess the effectiveness of oral collagen supplementation in improving skin elasticity and hydration based on current scientific literature. Material and methods: A literature review was conducted using the PubMed, Cochrane Library, and Google Scholar databases. Randomized controlled trials, meta-analyses, and systematic reviews published since 2018 that evaluated the effects of oral collagen supplementation on skin hydration and/or elasticity were included. Results: Most studies indicate that hydrolyzed collagen supplementation is associated with a moderate, statistically significant improvement in skin hydration and elasticity. More pronounced effects were reported for low-molecular-weight collagen peptides and supplementation lasting at least 8–12 weeks. However, analyses limited to studies of the highest methodological quality showed reduced effect sizes. Conclusion: Available evidence suggests that oral collagen peptides may support improvements in skin hydration and elasticity, although the magnitude of this effect remains uncertain. The most consistent benefits have been observed with low-molecular-weight preparations used for a minimum of 8–12 weeks. Further well-designed studies are required to determine optimal supplementation regimens.